PERBAIKAN AFASIA PADA STROKE SUBKORTIKAL PASCA rTMS - Amanda Tiksnadi* (NEURONA, 2015)
IS A MANIFESTATION OF LANGUAGE DISORDERS THAT COMMONLY RESULTS FROM DAMAGE TO CORTICAL PORTIONS OF THE BRAIN THAT ARE RESPONSIBLE FOR LANGUAGE RECENTLY APHASIA FOLLOWING LESIONS TO THE BASAL GANGLIA THALAMUS OR OTHER NONCORTICAL REGION HAS ALSO BEEN REPORTED IN SINGLE CASE REPORTS AND CASE SERIES PEOPLE WITH APHASIA HAVE A LONG RECOVERY PERIOD OF MONTHS OR YEARS MANY LIVE WITH MAJOR IMPAIRMENT IN COMMUNICATION FOR THE REST OF THEIR LIVES